EKSISTENSI MANUSIA DI ERA ARTIFICIAL INTELLIGENCE“PRESPEKTIF MUHAMMAD IQBAL” - Arrasikhu Fil'Ilmi (Mahiyah: Journal of Islamic Thought and Philosophy, 2026)
This article examines the problem of human existence in the era of Artificial Intelligence through the perspective of Muhammad Iqbal’s philosophy of khudi. The rapid development of AI has not only transformed human activities in education, communication, knowledge production, and decision-making, but has also raised fundamental philosophical questions concerning autonomy, creativity, moral responsibility, and the meaning of being human. This study employs a qualitative library research method with a hermeneutical-philosophical approach. Primary data are derived from Muhammad Iqbal’s concept of khudi, while secondary data are obtained from scholarly works on Artificial Intelligence, human autonomy, moral agency, Islamic philosophy, and contemporary technological ethics. The findings show that Iqbal’s khudi provides a critical framework for affirming human beings as active, creative, free, and morally responsible subjects. AI should not be positioned as an authority that replaces human consciousness, but as an instrument that supports human development. Therefore, strengthening khudi becomes essential to prevent humans from becoming passive objects of algorithmic systems and to preserve their dignity, spirituality, and existential responsibility.